2021
DOI: 10.3390/jcm10173788
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Motion in Degenerative Cervical Myelopathy: The Level of the Stenotic Segment and Gender Cause Altered Pathodynamics

Abstract: In degenerative cervical myelopathy (DCM), focally increased spinal cord motion has been observed for C5/C6, but whether stenoses at other cervical segments lead to similar pathodynamics and how severity of stenosis, age, and gender affect them is still unclear. We report a prospective matched-pair controlled trial on 65 DCM patients. A high-resolution 3D T2 sampling perfection with application-optimized contrasts using different flip angle evolution (SPACE) and a phase-contrast magnetic resonance imaging (MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Wolf et al reported an evaluation technique using a 3-dimensional hierarchical deep convolutional neural network (CNN) for anatomical segmentation and spinal cord motion measurements. 16,17 This approach appears promising, as motion evaluation could be conducted automatically after appropriate training of the CNN. However, it may be challenging to widely transfer this technique to other centers in order to foster clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolf et al reported an evaluation technique using a 3-dimensional hierarchical deep convolutional neural network (CNN) for anatomical segmentation and spinal cord motion measurements. 16,17 This approach appears promising, as motion evaluation could be conducted automatically after appropriate training of the CNN. However, it may be challenging to widely transfer this technique to other centers in order to foster clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical significance was set at <.05. Spinal cord motion values were compared in each cervical segment (C2 = segment C2/C3; C3 = segment C3/C4; C4 = segment C4/C5; C5 = segment C5/C6; C6 = segment C6/C7) separately, as previous work showed significant differences of spinal cord motion between the cervical segments 9,16 . At segment C7/T1, no comparison of axial and sagittal PC‐MRI was possible as no axial measurement was available.…”
Section: Methodsmentioning
confidence: 99%
“…In the compliant volume provided by the spinal canal and the non-compliant spinal cord, the cranial pressure pulse can lead to oscillatory inflow and outflow at velocities up to 10 mm/s at the cervical cord level, with the velocity depending on the spinal canal diameter at any given spinal level (33). The amplitude of the rostrocaudal movement of these pulsations is about 9 mm per cycle in the cervical CSF and about 4 mm at the thoraciclumbar junction, with minimal movement in the distal part of the lumbar sac.…”
Section: Factors Governing Spinal Oscillatory Csf Flowmentioning
confidence: 99%
“…Importantly, although poorly studied, eccentricities (lordosis and kyphosis) found in the human spine affect the magnitude and characteristics of slow bulk motion of CSF in the SSAS. Such deformities or other spinal injuries, leading to canal stenosis, can severely impact local solute redistribution (33,38).…”
Section: Spinal Cord Biomechanical Morphologymentioning
confidence: 99%
“…These changes were also correlated with mJOA and in the future could be used to further understand role of sex-hormones and prognostic factors in pathogenesis of DCM. Wolf et al [ 6 ] also found gender related differences in SC motion patterns amongst men with stenosis at the C5/C6 or C6/C7 levels and no relationship between cervical joint motion to severity of the stenosis indicating the need for further assessment of gender differences in pathological features of DCM. On assessment of outcome measures for DCM, Kadanka et al [ 7 ], showed that the standardized 10 m walk/run test can assess motor and balance abnormalities in both classic DCM patients and non-myelopathic degenerative cervical cord compression (NMDCC) patients, which has a 40% prevalence in 60+ age groups in European/American subpopulation.…”
mentioning
confidence: 99%